2021
DOI: 10.1016/j.psj.2021.101415
|View full text |Cite|
|
Sign up to set email alerts
|

The association of social rank with paternity efficiency in competitive mating flocks of Zi goose ganders (Anser cygnoides L.)

Abstract: The purpose of this study was to investigate the influence of social rank ( SR ) on paternity efficiency ( PE ) in competitive mating flocks of geese. Thirty ganders and 150 geese (Zi geese, Anser cygnoides L.) aged approximately one, were divided into 3 groups. Flock 1 included 10 ganders and 50 female geese, flock 2 included 11 ganders and 55 female geese, and flock 3 included 9 ganders and 45 female geese. The frequency of the agonistic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Consequently, eliminating aggressive male and uncooperative female geese before forming the groups may significantly improve the frequency of successful copulation. In addition, the reason for the differences between our results and those of previous studies could be attributable to the different breeds used in experiments [ 4 ]. Gumulka and Rozenboim also found that the sexual interactions in the mean range (0.4–0.8) from 9:00 to 12:00 a.m. and 1:00 to 4:30 p.m. were enough to meet the requirement for geese breeding [ 24 ].…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Consequently, eliminating aggressive male and uncooperative female geese before forming the groups may significantly improve the frequency of successful copulation. In addition, the reason for the differences between our results and those of previous studies could be attributable to the different breeds used in experiments [ 4 ]. Gumulka and Rozenboim also found that the sexual interactions in the mean range (0.4–0.8) from 9:00 to 12:00 a.m. and 1:00 to 4:30 p.m. were enough to meet the requirement for geese breeding [ 24 ].…”
Section: Discussioncontrasting
confidence: 93%
“…In terms of mating location, all these three goose breeds expressed a preference for mating on land. Another experiment also noted that high fertilization rates are sustained under waterless conditions, confirming their capacity to mate properly on land [ 4 ]. However, considering the waterless condition might increase the risk of phallus pecking and phallus hygiene problems, an enhanced approach to the management of geese should be required.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Experiment I: Following the protocol outlined by Zhang et al (2021) , semen samples were collected from 40 ganders on five occasions, once per week, and SM was assessed for each gander. Based on SM rankings, ganders were categorized into high- and low-sperm mobility rank ( SMR ) groups, comprising 3 ganders each with the highest and lowest SM, respectively.…”
Section: Methodsmentioning
confidence: 99%